2003
DOI: 10.1093/cercor/13.10.1072
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Complexity of Layer I in Human Cerebral Cortex

Abstract: In this study we examine possible origins and migratory routes of human cortical neurons, with special emphasis on the preplate and layer I. In embryonic stages, two main cell types, Cajal-Retzius cells, and cells labeled with interneuron markers (calretinin, calbindin and GABA), were present in the preplate layer. In addition, a number of preplate GABAergic cells co-expressed either Nkx2.1 or Dlx transcription factors, findings consistent with their origin in the ganglionic eminence and subsequent tangential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
133
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 77 publications
(103 reference statements)
18
133
2
Order By: Relevance
“…2 O-Q), the hESC-derived NE recapitulated the continuous self-formation of the cortex and LGE (striatum anlage) in adjacent positions as seen in vivo. The origin of human cortical interneurons may be an intriguing topic to be studied using this system, because they are suggested to arise not only from the subplallium but also from the cortical VZ/SVZ (31,32) in the human fetus.…”
Section: Discussionmentioning
confidence: 99%
“…2 O-Q), the hESC-derived NE recapitulated the continuous self-formation of the cortex and LGE (striatum anlage) in adjacent positions as seen in vivo. The origin of human cortical interneurons may be an intriguing topic to be studied using this system, because they are suggested to arise not only from the subplallium but also from the cortical VZ/SVZ (31,32) in the human fetus.…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic interneurons that are born in the ventral telencephalon reach the cortex by tangential migration [30; 44]. Interestingly, recent data have suggested that in primates, the majority of the cortical interneurons originate in the cortical ventricular and subventricular zones, and that there is a portion contributed by the ganglionic eminence of the ventral telencephalon [45][46][47]. We show here that differentiated hc-NSCs give rise to glutamatergic (10%) and a smaller population of GABAergic cells (about 1%).…”
Section: Discussionmentioning
confidence: 99%
“…These findings clearly show that an initial description of the subplate as layer VIb in the fetal cat (Marin-Padilla, 1971, 1972, 1978 was overly simplified and that it at best can only be applied to the first (earliest generated) wave of subplate neurons. For a detailed criticism of this original concept of the primordial plexiform layer (or preplate) see a recent review (Bystron et al 2008) as well as a number of recent studies which pointed out a previously unsuspected complexity of the early neocortical anlage in humans (Zecevic et al 1999;Meyer et al 2000;Zecevic & Rakic, 2001;Rakic & Zecevic, 2003;Bystron et al 2005Bystron et al , 2006 as well as in rodents (Rickmann et al 1977;Hevner et al 2003;Jimé nez et al 2003;Bielle et al 2005;García-Moreno et al 2007). …”
Section: )mentioning
confidence: 99%